High-wear-resistance coating based on nano-graphene and preparation method of high-wear-resistance coating

By using nanographene and other materials in the coating, the wear and corrosion problems of the material surface under frictional corrosion conditions are solved, high wear resistance and conductivity are achieved, extending service life and reducing maintenance costs.

CN119264763AInactive Publication Date: 2025-01-07SUZHOU HONGZHONG TECHNOLOGY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202410535548.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-04-30
Publication Date
2025-01-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the wear and corrosion problems of material surfaces under frictional corrosion conditions, especially fatigue cracks and contact resistance changes caused by frictional corrosion caused by objects contact and relative movement at high temperatures.

Method used

Using a high wear-resistant coating based on nanographene, by combining nanographene with epoxy resin, phenolic resin, polyester resin, micron-scale silicon carbide, cartilage, alumina ceramics, high manganese steel and additives, through Ultrasonic treatment or mechanical stirring are uniformly dispersed to form a coating with high wear resistance and electrical conductivity.

Benefits of technology

Through the high strength and conductivity of graphene, the coating significantly improves the wear resistance and conductivity of the material surface, extends the service life, reduces maintenance costs, and provides certain protection in chemical corrosion, reducing the environment. pollute.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a high-wear-resistance coating based on nano graphene and a preparation method of the high-wear-resistance coating, and relates to the technical field of coatings. The high-wear-resistance coating based on nano graphene comprises the following raw materials in parts by weight: 10-15 parts of epoxy resin, 1-10 parts of phenolic resin, 1-10 parts of polyester resin, 1-3 parts of nano graphene, 3-5 parts of micron-sized silicon carbide, 1-3 parts of carborundum, 1-5 parts of a dispersing agent, 1-5 parts of aluminum oxide ceramic, 1-5 parts of high manganese steel, 1-5 parts of an auxiliary agent and 76-105 parts of a composite solvent, the particle size of the nano graphene is 20-100 microns, and the particle size of the carborundum is 50-200 microns. The coating has excellent wear resistance due to high strength and toughness of graphene, the surface of a coated object can be protected from wear and corrosion, the service life of the object under the coating can be prolonged, the maintenance cost and the replacement frequency can be reduced, the coating can conduct current under the coating due to high conductivity of graphene, and the service life of the coating is prolonged. The method is suitable for application scenarios requiring conductive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, in particular to a high-wear-resistant coating based on nanographene and a preparation method thereof. Background Art

[0002] Graphene can be seen as a single layer of exfoliated graphite, with a thickness of only one carbon atom layer (0.35 nm). The carbon atoms are arranged in a hexagonal ring, and each carbon atom is closely connected to the other three carbon atoms through a σ bond. The CC bond gives graphene excellent mechanical properties. The strong interaction between carbon atoms makes it the material with the highest mechanical strength known so far, and it can be widely used as an additive in new high-strength composite materials.

[0003] Graphene has superhard properties (110GPa), which is harder than diamond. Graphene also has super high strength, which is 100 times higher than the best steel in the world. At the same time, it has good elasticity and can stretch up to 20% of its own size. Although it is very strong, it is as flexible as plastic packaging and can be bent, folded or rolled up like a scroll. The thermal conductivity of graphene far exceeds that of all other materials. Adding one thousandth of graphene to plastic can increase the heat resistance of plastic by 30°C. In addition, graphene also has excellent lubricity and corrosion resistance. The combination of graphene microsheets and other materials can greatly improve the lubricity and corrosion resistance of many materials, and the performance of the materials will be greatly improved.

[0004] The tribocorrosion theory holds that when an object moves along the tangent direction of the contact surface or has a tendency to move relative to another object at high temperature, there is a friction force between the contact surfaces of the two objects that hinders their relative movement. If friction is also accompanied by corrosion, the harm caused cannot be ignored. Studies have found that the oxides produced by tribocorrosion on the friction matrix can cause local stress, fatigue cracks, and even adhesion, and may also change the contact resistance, thereby affecting the function of the weak current relay. There are two mechanisms for producing this type of tribocorrosion: wear-oxidation and oxidation-wear. The tribocorrosion theory holds that on the compressed metal interface, some tiny protrusions are cold-welded, and then during the relative movement, the cold-welded area is partially broken to form very small metal debris, which is oxidized again due to the heat of tribocorrosion. This process is repeated to form small pits or grooves on the interface and accumulate oxide debris. There is a theory that most metal surfaces have an oxide film. The oxide film of some tiny protrusions breaks into pieces under high pressure, and the exposed fresh surface is re-oxidized or cold-welded. Then, during the relative movement, the cold-welded area or the oxide film is partially broken, and the friction corrosion heat oxidizes the metal or metal fragments again. This process is repeated, causing damage to the contact surface. It can be seen that the basic conditions for friction corrosion to occur are that the contact surface must bear a load, there must be vibration or repeated relative movement between the contact surfaces, and the load and relative movement of the contact surface are sufficient to cause the surface to slide or deform. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a high wear-resistant coating based on nanographene and a preparation method thereof, which solves the problems arising from friction on the material surface in the above-mentioned friction corrosion theory.

[0006] To achieve the above purpose, the present invention is implemented through the following technical scheme: a high wear-resistant coating based on nanographene, comprising the following raw materials in parts by weight: 10-15 parts of epoxy resin, 1-10 parts of phenolic resin, 1-10 parts of polyester resin, 1-3 parts of nanographene, 3-5 parts of micron-sized silicon carbide, 1-3 parts of corundum, 1-5 parts of dispersant, 1-5 parts of alumina ceramics, 1-5 parts of high manganese steel, 1-5 parts of additives, and 76-105 parts of composite solvents, wherein the nanographene particle size is 20-100 microns, and the corundum particle size is 50-200 microns.

[0007] Preferably, the dispersant is silicate (such as water glass) and alkali metal phosphate (such as sodium tripolyphosphate, sodium hexametaphosphate and sodium pyrophosphate).

[0008] Preferably, the composite solvent is composed of 25-35 parts of N'N-dimethylacetamide, 25-35 parts of N-methylpyrrolidone, 25-35 parts of toluene and 1-10 parts of butanone.

[0009] Preferably, the auxiliary agent includes: one or more of a coupling agent, a wetting and dispersing agent, a defoaming agent, a deaerator, a leveling agent, a pH regulator, and a thickener; the coupling agent includes a mixture of one or more of silanes, titanates, and aluminate compounds; the leveling agent is an acrylic leveling agent, a fluorine leveling agent, or an organosilicon leveling agent; the defoaming agent is an organosiloxane, a polyether, a silicon and ether graft, or an amine.

[0010] Preferably, a method for preparing a highly wear-resistant coating based on nanographene comprises the following steps: S1: Raw material preparation Prepare the required raw materials, including epoxy resin, phenolic resin, polyester resin, nanographene, micron-sized silicon carbide, corundum, dispersant, alumina ceramics, high manganese steel, additives, and composite solvents; S2: Nanographene dispersion Dispersing the nanographene into the solvent may be carried out by ultrasonic treatment, mechanical stirring or high shear force dispersion method to ensure that the graphene is uniformly dispersed in the solvent; S3: Polymer matrix preparation The polymer matrix is ​​mixed with the solvent and stirred and heated under appropriate conditions to ensure that the polymer is completely dissolved in the solvent to form a uniform solution; S4: Nanographene mixed with polymer matrix Slowly adding the dispersed nanographene solution into the polymer matrix solution and stirring sufficiently to ensure that the nanographene is evenly dispersed in the polymer matrix; S5: Addition of crosslinking agent According to the need, a proper amount of cross-linking agent is added to the mixed solution to improve the mechanical properties and wear resistance of the coating; S6: Coating Preparation The prepared mixed solution is filtered or centrifuged to remove possible impurities and aggregated graphene particles to obtain a uniform coating.

[0011] The present invention provides a high wear-resistant coating based on nanographene and a preparation method thereof. It has the following beneficial effects: The present invention uses the high strength and toughness of graphene to make the coating have excellent wear resistance, which can protect the surface of the coated object from wear and corrosion. This coating can extend the service life of the object under the coating, reduce maintenance costs and replacement frequency. The high conductivity of graphene enables the coating to conduct current under the coating, which is suitable for application scenarios that require conductive properties.

[0012] The present invention uses epoxy resin as the main component to prevent stress damage caused by excessive hardness of the surface of the coating after film formation. The nanographene coating may have a certain resistance to chemical corrosion and protect the objects under the coating from erosion by chemical media. The nanographene coating can be designed to be solvent-free or low-volatile organic matter, which helps to reduce pollution to the environment. DETAILED DESCRIPTION

[0013] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example

[0014] The embodiment of the present invention provides a high wear-resistant coating based on nanographene, comprising the following raw materials in parts by weight: 10 parts of epoxy resin, which is usually composed of epoxy groups and functional groups such as active bisphenols, 1 part of phenolic resin, which is a thermosetting resin, usually prepared by the condensation reaction of phenol and aldehyde compounds (such as formaldehyde), 1 part of polyester resin, which is an important polymer material, prepared by polymerization reaction, and mainly formed by esterification reaction of acid anhydride and alcohol anhydride, 1 part of nanographene, and 3 parts of micron-sized silicon carbide, which is a high-temperature resistant and corrosion-resistant ceramic material with excellent thermal conductivity. Conductivity and mechanical properties, 1 part of corundum, 1 part of dispersant, 1 part of alumina ceramics, alumina ceramics is a ceramic material made of aluminum oxide (Al2O3), with excellent wear resistance, high temperature resistance and chemical stability, 1 part of high manganese steel, high manganese steel is a steel containing a high proportion of manganese, usually containing more than 10% manganese, it has excellent wear resistance, impact resistance and hardness, 1 part of additives, 76 parts of composite solvents, among which, the nanographene particle size is 20 microns, nanographene is a two-dimensional material composed of carbon atoms, with excellent electrical conductivity, thermal conductivity and mechanical strength. The corundum particle size is 50 microns, corundum is a mineral with extremely high hardness, and its main component is silicon dioxide.

[0015] The dispersant is a silicate (such as water glass).

[0016] The composite solvent consists of 25 parts of N'N-dimethylacetamide, 25 parts of N-methylpyrrolidone, 25 parts of toluene and 1 part of butanone.

[0017] The additives include: one or more of coupling agents, wetting and dispersing agents, defoaming agents, air release agents, leveling agents, pH regulators, and thickeners; the coupling agent includes a mixture of one or more of silanes, titanates, and aluminate compounds; the leveling agent is an acrylic leveling agent, a fluorine leveling agent, or an organosilicon leveling agent; the defoaming agent is an organosiloxane, polyether, silicon and ether grafted or amine.

[0018] A method for preparing a highly wear-resistant coating based on nanographene comprises the following steps: S1: Raw material preparation Prepare the required raw materials, including epoxy resin, phenolic resin, polyester resin, nanographene, micron-sized silicon carbide, corundum, dispersant, alumina ceramics, high manganese steel, additives, and composite solvents; S2: Nanographene dispersion Dispersing the nanographene into the solvent may be carried out by ultrasonic treatment, mechanical stirring or high shear force dispersion method to ensure that the graphene is uniformly dispersed in the solvent; S3: Polymer matrix preparation The polymer matrix is ​​mixed with the solvent and stirred and heated under appropriate conditions to ensure that the polymer is completely dissolved in the solvent to form a uniform solution; S4: Nanographene mixed with polymer matrix Slowly adding the dispersed nanographene solution into the polymer matrix solution and stirring sufficiently to ensure that the nanographene is evenly dispersed in the polymer matrix; S5: Addition of crosslinking agent According to the need, a proper amount of cross-linking agent is added to the mixed solution to improve the mechanical properties and wear resistance of the coating; S6: Coating Preparation The prepared mixed solution is filtered or centrifuged to remove possible impurities and aggregated graphene particles to obtain a uniform coating. Example

[0019] The embodiment of the present invention provides a high wear-resistant coating based on nanographene, comprising the following raw materials in parts by weight: 15 parts of epoxy resin, 10 parts of phenolic resin, 10 parts of polyester resin, 3 parts of nanographene, 5 parts of micron-sized silicon carbide, 3 parts of corundum, 5 parts of dispersant, 5 parts of alumina ceramics, 5 parts of high manganese steel, 5 parts of additives, and 105 parts of composite solvents, wherein the nanographene particle size is 100 microns, and the corundum particle size is 200 microns; the high strength and toughness of graphene make the coating have excellent wear resistance, can protect the surface of the coated object from wear and corrosion, this coating can extend the service life of the object under the coating, reduce maintenance costs and replacement frequency, and the high conductivity of graphene enables the coating to conduct current under the coating, which is suitable for application scenarios requiring conductive properties.

[0020] The dispersant is an alkali metal phosphate (such as sodium tripolyphosphate).

[0021] The composite solvent consists of 35 parts of N'N-dimethylacetamide, 35 parts of N-methylpyrrolidone, 35 parts of toluene and 10 parts of butanone.

[0022] The additives include: one or more of coupling agents, wetting and dispersing agents, defoaming agents, air release agents, leveling agents, pH regulators, and thickeners; the coupling agent includes a mixture of one or more of silanes, titanates, and aluminate compounds; the leveling agent is an acrylic leveling agent, a fluorine leveling agent, or an organosilicon leveling agent; the defoaming agent is an organosiloxane, a polyether, a silicon and ether graft, or an amine; the coupling agent is used to improve the bonding properties of different materials, the wetting and dispersing agent helps dissolve and disperse solid particles, the defoaming agent and air release agent can control the generation and removal of bubbles in the liquid, the leveling agent can improve the flatness of the coating surface, the pH regulator is used to adjust the pH of the solution, and the thickener is used to increase the viscosity of the liquid.

[0023] A method for preparing a highly wear-resistant coating based on nanographene comprises the following steps: S1: Raw material preparation Prepare the required raw materials, including epoxy resin, phenolic resin, polyester resin, nanographene, micron-sized silicon carbide, corundum, dispersant, alumina ceramics, high manganese steel, additives, and composite solvents; S2: Nanographene dispersion Dispersing the nanographene into the solvent may be carried out by ultrasonic treatment, mechanical stirring or high shear force dispersion method to ensure that the graphene is uniformly dispersed in the solvent; S3: Polymer matrix preparation The polymer matrix is ​​mixed with the solvent and stirred and heated under appropriate conditions to ensure that the polymer is completely dissolved in the solvent to form a uniform solution; S4: Nanographene mixed with polymer matrix Slowly adding the dispersed nanographene solution into the polymer matrix solution and stirring sufficiently to ensure that the nanographene is evenly dispersed in the polymer matrix; S5: Addition of crosslinking agent According to the need, a proper amount of cross-linking agent is added to the mixed solution to improve the mechanical properties and wear resistance of the coating; S6: Coating Preparation The prepared mixed solution is filtered or centrifuged to remove possible impurities and aggregated graphene particles to obtain a uniform coating.

[0024] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A highly wear-resistant coating based on nanographene, characterized in that: The invention comprises the following raw materials in parts by weight: 10-15 parts of epoxy resin, 1-10 parts of phenolic resin, 1-10 parts of polyester resin, 1-3 parts of nanographene, 3-5 parts of micron-sized silicon carbide, 1-3 parts of corundum, 1-5 parts of dispersant, 1-5 parts of alumina ceramics, 1-5 parts of high manganese steel, 1-5 parts of auxiliary agent and 76-105 parts of composite solvent, wherein the particle size of the nanographene is 20-100 microns, and the particle size of the corundum is 50-200 microns.

2. A highly wear-resistant coating based on nanographene according to claim 1, characterized in that: The dispersants are silicates (such as water glass) and alkali metal phosphates (such as sodium tripolyphosphate, sodium hexametaphosphate and sodium pyrophosphate).

3. A highly wear-resistant coating based on nanographene according to claim 1, characterized in that: The composite solvent is composed of 25-35 parts of N'N-dimethylacetamide, 25-35 parts of N-methylpyrrolidone, 25-35 parts of toluene and 1-10 parts of butanone.

4. The high wear-resistant coating based on nanographene according to claim 1, characterized in that: The auxiliary agent includes: one or more of a coupling agent, a wetting and dispersing agent, a defoaming agent, a deaerator, a leveling agent, a pH regulator, and a thickener; the coupling agent includes a mixture of one or more of silanes, titanates, and aluminate compounds; the leveling agent is an acrylic leveling agent, a fluorine leveling agent, or an organosilicon leveling agent; the defoaming agent is an organosiloxane, a polyether, a silicon and ether graft, or an amine.

5. A method for preparing a highly wear-resistant coating based on nanographene, characterized in that: The following steps are involved: S1: Raw material preparation Prepare the required raw materials, including epoxy resin, phenolic resin, polyester resin, nanographene, micron-sized silicon carbide, corundum, dispersant, alumina ceramics, high manganese steel, additives, and composite solvents; S2: Nanographene dispersion Dispersing the nanographene into the solvent may be carried out by ultrasonic treatment, mechanical stirring or high shear force dispersion method to ensure that the graphene is uniformly dispersed in the solvent; S3: Polymer matrix preparation The polymer matrix is ​​mixed with the solvent and stirred and heated under appropriate conditions to ensure that the polymer is completely dissolved in the solvent to form a uniform solution; S4: Nanographene mixed with polymer matrix Slowly adding the dispersed nanographene solution into the polymer matrix solution and stirring sufficiently to ensure that the nanographene is evenly dispersed in the polymer matrix; S5: Addition of crosslinking agent According to the need, a proper amount of cross-linking agent is added to the mixed solution to improve the mechanical properties and wear resistance of the coating; S6: Coating Preparation The prepared mixed solution is filtered or centrifuged to remove possible impurities and aggregated graphene particles to obtain a uniform coating.

Citation Information

Cited By

  • Modified wear-resistant anticorrosive resin coating and preparation method thereof

    CN121108845A